2017
DOI: 10.1038/srep41934
|View full text |Cite
|
Sign up to set email alerts
|

Acellular Urethra Bioscaffold: Decellularization of Whole Urethras for Tissue Engineering Applications

Abstract: Patients with stress urinary incontinence mainly suffer from malfunction of the urethra closure mechanism. We established the decellularization of porcine urethras to produce acellular urethra bioscaffolds for future tissue engineering applications, using bioscaffolds or bioscaffold-derived soluble products. Cellular removal was evaluated by H&E, DAPI and DNA quantification. The presence of specific ECM proteins was assessed through immunofluorescence staining and colorimetric assay kits. Human skeletal muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 55 publications
(90 reference statements)
1
40
0
Order By: Relevance
“…Another application of decellularized ECM is improvement in the biological properties of synthetic materials [ 11 ] or fabrication of hydrogels [ 12 15 ]. Decellularization techniques have been successfully used for a variety of organs including the heart [ 16 ], blood vessels [ 17 ], urethra [ 18 ], urinary bladder [ 19 ], kidney [ 20 , 21 ], trachea [ 22 ], lung [ 23 ], skeletal muscle [ 24 ], liver [ 25 ], and gastrointestinal tract [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another application of decellularized ECM is improvement in the biological properties of synthetic materials [ 11 ] or fabrication of hydrogels [ 12 15 ]. Decellularization techniques have been successfully used for a variety of organs including the heart [ 16 ], blood vessels [ 17 ], urethra [ 18 ], urinary bladder [ 19 ], kidney [ 20 , 21 ], trachea [ 22 ], lung [ 23 ], skeletal muscle [ 24 ], liver [ 25 ], and gastrointestinal tract [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, Triton X‐100 has been reported to be the best decellularizing agent compared with other detergents and that for many tissues and organs including ligaments, small intestine, annulus fibrosus, liver and aortic valves . On the other hand, some studies demonstrated that Triton X‐100 had poor cell removal capacity for many tissues and organs such as veins, cornea, urethra, heart and kidneys …”
Section: Chemicals Used For Decellularizationmentioning
confidence: 99%
“…SDS incorporates into the outer membrane layer by increasing its curvature, creating a stress which results in the membrane disruption . SDS proved to be superior when compared with other detergents in removing cells and genetic materials in many tissues and organs including aorta, veins, heart, kidneys and urethra . Triton X‐100 and SDS have also shown negative influence on tissues and organs used for decellularization but, on the other hand, when these two detergents were used in combination, the mixture allowed efficient decellularization and preservation of ECM structures and this has been tested on tendons, kidneys, SIS, and liver …”
Section: Chemicals Used For Decellularizationmentioning
confidence: 99%
See 2 more Smart Citations